An Analysis of Transportation Management of Beer Brewing Business in Thailand: A Case Study Beer Company - เรืองเทพ จุฬาภรณ์; อังยุรีกุล นงนุช (Asian Journal of Applied Economics, 2013)
Abstract The objectives of this study were beer brewing business and transportation activity of beer brewing business in Thailand by using a case study: Beer Company. Cost analysis was done for every step during transportation process. The factors affecting distribution cost was studied. According to the study, the structure of transportation within the transportation division of Beer Company could be divided into 2 sections: Beer in box and fresh beer. The company calculated cost by using the conventional accounting method but it caused the error. When the activity base costing system was applied, transportation process could be divided into 9 activities. There were 15 cost items during the transportation process. Cost was assigned to different steps using the optimum cost pusher. The activity base costing system could reduce the error of the conventional method. Factors affecting the transportation cost were fuel and allowance. Therefore the company should revise structure of transportation division and use activity base costing together with the conventional accounting method to calculate the transportation cost. Alternated way to transport should be considered. Keywords: Transportation Management